Analisis Pengaruh Permodalan, Pemasaran, Teknologi & Inovasi, Kecerdasan Spiritual dan Perencanaan Strategi Terhadap Kinerja Usaha Kecil Menengah (UKM) Mebel di Klaten Jawa Tengah - Lasminiasih Lasminiasih; Rooswhan Budhi Utomo; Sigit Nurdianto (Universitas Negeri Surabaya, 2018)
Small medium enterprises (SMEs) constitute a business activity that is able to expand employment and provide economic services broadly to society and can play a role in the process of Equalization and the increase in people's income, encouraging the growth of economy and play a role in realizing stability nationwide. The purpose of this research is to know the influence of the capital, marketing, technology and innovation, spiritual intelligence and planning strategy on performance of small medium-sized enterprise (SMEs) furniture in Klaten, Central Java. The object of the research done in the village of Dayan, Ceper, Klaten, Central Java. The methods used in this research are multiple linear regression by disseminating a questionnaire in directly. The results showed that capital, marketing, technology and innovation, spiritual intelligence and planning strategy of the influence on the performance of small and medium businesses (SMEs) furniture in the Klaten.